THE ROLE OF ANAESTHETIST IN THE MANAGEMENT OF PATIENTS DUE TO INSURGENCY IN THE NORTH-EASTERN NIGERIA - Adamu SA; Usman BD; Bakari AA; Yauba MS; Dabkana T; Tela UM; Ngamdu YB (Ntec Specialist, 2013)
Background: The roles played by the team of Anaesthetists in the management of patients due to insurgency are enormous and very vital in the survival of the patients and indeed in the reduction of the possible morbidities and mortalities due to injuries from the insurgency. Objective: This study is aimed at giving an overview of the role of Anaesthetist in important areas of patient's management due to insurgency and to suggest ways of improvement. Method: This is a prospective study of 1,339 patients managed for various injuries sustained due to insurgency in the University of Maiduguri Teaching Hospital, Maiduguri, Borno State, Nigeria, for the period of five years (January, 2010 and December, 2014). Results: One thousand three and thirty nine (1,339) patients who were injured directly due to the insurgency were included in the study during the period under review. Their ages ranged from 1 month to 80 years with the mean age of 38.6±18.3 years. Most of the injuries occurred among the age group 18 - 35 years. Patients were resuscitated, had anaesthesia for surgeries and also had intensive care management. Conclusion: The roles played by the Anaesthetist are so vital in the survival of the patients due to insurgency. However, there is a need for an increase in the number of Anaesthesia manpower and for the training and re-training of these Anaesthetists in the management of mass casualties